Investigation and Analysis of Eye Discomfort Caused by Video Display Terminal Use Among Medical Students Studying at High-Altitude Regions - Liu, Bingjie; Jiang, Shanshan; Li, Zuyou; Wang, Yao; Zhou, Daijiao; Chen, Zhen (Frontiers in Public Health, 2022)
Objective To investigate the use of video display terminal (VDT) in high-altitude regions by medical students and the resulted risk factors of eye discomfort. Methods A cross-sectional study was conducted in 686 medical students randomly selected from high-altitude regions, Kunming, Yunnan Province. The prevalence of video display terminal syndrome (VDTs) and related risk factors in medical students were analyzed by instructing students to fill in the eye discomfort symptom questionnaire [Ocular Surface Disease Index (OSDI) scale]. Results There were 686 participants in this study, including 213 males (31.0%) and 473 females (69.0%). The results of questionnaire survey showed that 184 patients (26.8%) didn't have eye discomfort symptoms and 502 patients (73.2%) had eye discomfort symptoms. The comparison of demographic and ocular characteristics of eye discomfort symptoms group and no eye discomfort symptoms group showed that medical students in the group with ocular discomfort symptoms had longer total duration of video terminal use, longer duration of each VDT use, higher total scores of ocular discomfort symptom scores, and a higher percentage of the ocular discomfort severity group, all with statistically significant differences. There was no significant difference in the remaining parameters between the two groups of participants. The results of multivariate logistic regression model analysis showed that the relationship between total sleep time, total duration of VDT use and eye discomfort symptom score was statistically significant (P < 0.05). Besides, ordinal logistic regression was applied further to investigate related factors of the severity of eye discomfort. The model demonstrated that total sleep duration and total VDT using duration were significantly associated with the severity of eye discomfort symptom (P < 0.05).The severity of eye discomfort symptom was significantly negatively related to the increased total sleep duration and it was significantly positively related to the increased VDT use duration. Conclusion The prevalence of VDTs is high in medical students at high-altitude regions. The longer total duration of daily use of VDT and shorter sleep duration are risk factors associated with VDTs. The severity of eye discomfort symptom was significantly negatively related to the increased total sleep duration and it was significantly positively related to the increased total VDT using duration.